Analysis of Social Stigma in Film Nomadland (2020) - Aisya Nurramadhany; Imelda Jelianti Manalu; Muhammad Aris Musthafa; Muhammad Rafiuddin; Fadhil Taufiq (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Nomadland (2020) film directed by Chloé Zhao, dives deep into the world of modern nomads in America after the recession, inspired by Jessica Bruder's real-life research. This study uses a thematic approach to unpack how the movie portrays stigma, increasing in on issues like financial struggles, loneliness, and feeling pushed to the edges of society. By closely examining the story, conversations, camera work, and audio, it shows how the film pushes back against the shame society loads on these nomads, while celebrating their strength and grit. What stands out is how stigma shows up as outright rejection and treating people like they're less than human, but the movie flips that by making the characters feel real and alive, and by pointing out the bigger unfair systems at play. This has broader currents for talks about how media and society treat marginalized folks, stressing why we need more compassion for those on the fringes. Overall, it adds to our understanding of movies and stigma by showing how film can break down harmful stereotypes